2008
DOI: 10.1017/s1041610208007266
|View full text |Cite
|
Sign up to set email alerts
|

The needs of people with dementia in care homes: the perspectives of users, staff and family caregivers

Abstract: Users' views on their needs should be sought even when the person has dementia and lives in a care home. Reliance solely on assessment by staff or carers may lead to under recognition of unmet needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 13 publications
8
86
1
2
Order By: Relevance
“…carpet bowling, gardening, music, bingo and crafts). As such this reinforces findings that meaningful activities were important to people with dementia in care homes (Hancock, Woods, Challis, & Orrell, 2006;Orrell et al, 2008). Getting out and about, whether this was in the care home building and garden or on structured outings has also been reported previously as an important design feature (Chalfont, 2008) and important to people with dementia (Duggan et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…carpet bowling, gardening, music, bingo and crafts). As such this reinforces findings that meaningful activities were important to people with dementia in care homes (Hancock, Woods, Challis, & Orrell, 2006;Orrell et al, 2008). Getting out and about, whether this was in the care home building and garden or on structured outings has also been reported previously as an important design feature (Chalfont, 2008) and important to people with dementia (Duggan et al, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Talking to people with dementia about what they like about a care home, when it happens, tends to focus on the quality of care experienced or the perceived quality of life that care home living provides (Harmer & Orrell, 2008;Orrell et al, 2008;Train, Nurock, Kitchen, Manela, & Livingston, 2005). Asking people with dementia their views on the building where they live is a new area our study set out to explore.…”
Section: What People With Dementia and Their Families Had To Say Aboumentioning
confidence: 99%
“…However, previous findings demonstrate that unmet needs in the oldest old often remain underdetected and undertreated [9]. Up to date, only a few studies, mostly focusing on residential care settings, examined the care needs of older patients suffering from dementia [7,8,11,12,15,16,17,18,19,20]. However, little is known about the unmet needs of the oldest old with MCI and dementia as assessed from various perspectives in the primary care setting in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…A quick glance through an issue of International Psychogeriatrics pulled from my shelves at random (20 (5), October 2008), revealed that of 16 review or original research articles, five (31%) (Lyketsos et al, 2008;Mendes-Chiloff et al, 2008;Milne et al, 2008;Nakaaki et al, 2008;Orrell et al, 2008) cited Folstein's MMSE. It therefore caused me little surprise to find that that the valuable contribution of Han et al (2000) in establishing a typical rate of decline for AD patients assessed with the MMSE had received the equal sixth highest number of citations of any paper published in the journal up to the end of 2006.…”
Section: Commentarymentioning
confidence: 99%